Earthquake engineering for concrete dams : analysis, design, and evaluation - Chopra, Anil K. (Hoboken, NJ, USA : Wiley-Blackwell, 2019)
"Written by one of the world's foremost authorities on concrete dams, this book provides a comprehensive overview of the analysis, response, design and safety evaluation of concrete dams under earthquake loading, for professional engineers and regulatory bodies"--
Includes bibliographical references and index.
Keywords: Concrete dams -- Earthquake effects; Dam safety; Earthquake engineering; Earthquake hazard analysis